2015
DOI: 10.1016/j.physletb.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Toward a solution to the R and v2 puzzle for heavy quarks

Abstract: The two key observables related to heavy quarks that have been measured in RHIC and LHC energies are the nuclear suppression factor RAA and the elliptic flow v2. Simultaneous description of these two observables is a top challenge for all the existing models. We have highlighted how a consistent combination of four ingredients i.e the temperature dependence of the energy loss, full solution of the Boltzmann collision integral for the momentum evolution of heavy quark, hadronization by coalescence, then the had… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
189
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(203 citation statements)
references
References 82 publications
14
189
0
Order By: Relevance
“…It has been suggested that heavy quarks produced by the gluon splitting process may experience different medium modification pattern compared to those directly produced through the hard scatterings [77]. As discussed earlier, by increasing the relative contribution of energy loss near T c , the heavy quark v 2 may be increased a lot without affecting its overall suppression [73,74]; this might be helpful to explain the large v 2 puzzle. These aspects will be explored in our future work.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that heavy quarks produced by the gluon splitting process may experience different medium modification pattern compared to those directly produced through the hard scatterings [77]. As discussed earlier, by increasing the relative contribution of energy loss near T c , the heavy quark v 2 may be increased a lot without affecting its overall suppression [73,74]; this might be helpful to explain the large v 2 puzzle. These aspects will be explored in our future work.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, it has been suggested in Refs. [73,74] that by taking into account the temperature dependence of the transport coefficient (q/T 3 ) and increasing the relative contribution of the medium modification to heavy flavor spectra around T c , the anisotropy parameter v 2 in the final state can be effectively enhanced. These effects will be investigated in detail in the future.…”
Section: Evolution Of Heavy Mesons In a Hadron Gasmentioning
confidence: 99%
“…Note that while obtaining effective Vlasov-Dupree equation in Eq. (18). The operator L 2 is defined as:…”
Section: Effective Transport Equation In Turbulent Chromo Fieldsmentioning
confidence: 99%
“…To address this, one requires to describe the dynamics of the HQs propagating through the QGP. Therefore, one can explore the physics of the HQ transport [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the QGP medium as follows.The non-equilibrated HQs can travel in the equilibrated QGP medium, and one has to deal the problem within the framework of Langevin dynamics [22]. This is to say that the HQs perform random motion in the equilibrated QGP.…”
Section: Introductionmentioning
confidence: 99%
“…However all the approaches show some difficulties to describe both the nuclear modification factor and the elliptic flow simultaneously. To study the time evolution of R AA and v 2 we have solved the Fokker Planck (FP) equation stochastically in terms of the Langevin equation, for detail we refer to our previous work [11]. The evolution of the bulk is provided by a 3+1D relativistic transport code tuned at fixed η/s [18] which is able to reproduce the same results of hydrodynamical simulations.…”
Section: Introductionmentioning
confidence: 99%